2014
DOI: 10.1007/s11239-014-1130-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of thromboelastography and rapid thromboelastography to assess the pharmacodynamic effects of vitamin K antagonists

Abstract: Thromboelastography (TEG) measures the effects of antithrombotic agents by assessing global functional clotting status by evaluating the viscoelastic properties of in vitro clot formation. Recently, rapid TEG (r-TEG), which uses tissue factor in addition to standard kaolin to accelerate activation of the clotting cascade, has been proposed to obtain more immediate results. The correlation between results of TEG or r-TEG with international normalized ratio (INR) in patients on vitamin K antagonist (VKA) therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
(79 reference statements)
1
16
2
Order By: Relevance
“…162 Detection of warfarin and novel oral anticoagulants (NOACs) is similarly unreliable, due to the fact that the test is run with added reagents that mask the presence of an anticoagulant. [163][164][165] Titrated NOAC added to blood samples ex vivo can be used to develop a standard curve for VEM assays, 166 and in other studies, well defined cohorts of patients taking a single drug had blood collected at a prescribed interval post-administration with effective differentiation of drug vs placebo. [167][168][169] Unfortunately, these experiments are limited by the homogeneity of samples assessed and development of real-world thresholds in the setting of trauma with variable renal function and unknown dose administration time, agent, etc.…”
Section: Role In Patients Taking Antiplatelet/ Anticoagulationmentioning
confidence: 99%
“…162 Detection of warfarin and novel oral anticoagulants (NOACs) is similarly unreliable, due to the fact that the test is run with added reagents that mask the presence of an anticoagulant. [163][164][165] Titrated NOAC added to blood samples ex vivo can be used to develop a standard curve for VEM assays, 166 and in other studies, well defined cohorts of patients taking a single drug had blood collected at a prescribed interval post-administration with effective differentiation of drug vs placebo. [167][168][169] Unfortunately, these experiments are limited by the homogeneity of samples assessed and development of real-world thresholds in the setting of trauma with variable renal function and unknown dose administration time, agent, etc.…”
Section: Role In Patients Taking Antiplatelet/ Anticoagulationmentioning
confidence: 99%
“…As discussed being a cumbersome and time consuming technique 2DE could not reach the clinics, however, Mass spectrometry, especially MALDI-TOF have successfully made its way to pathology labs in the present decade. Several diseases like cancer, Alzheimer's disease, Amyloid lateral sclerosis, renal amyloidosis, and Severe combined immunodeficiency can now be diagnosed using mass spectrometry and its variants [28][29][30][31][32][33][34].…”
Section: Proteomics In Clinical Diagnosis -Presentmentioning
confidence: 99%
“…Small studies thus far have differing results regarding the utility of TEG in patients on oral anticoagulants. For instance, Franchi et al demonstrated that in 100 patients taking vitamin K antagonists (VKA) there was a correlation between the following r-TEG times and INR: ACT, R time, time to maximum rate of thrombus generation (TMRTG) time, but not with the maximum rate of thrombus generation (MRTG) time [16]. Rathbun et al, however, performed a prospective study of 22 patients taking rivaroxaban, and demonstrated no correlation to TEG findings [17].…”
Section: Limitations Of Tegmentioning
confidence: 99%
“…Summary of papers chosen for discussion Castilo et al[16] 64 patients with ICH compared to human controls. ICH patients had faster clot formation compared to controls.…”
mentioning
confidence: 99%